Interfaces between rural education and agroecology in rural settlement areas in the state of paraná - Borges, Marizete; Marcelites, Elder José [UNESP]; Finatto, Roberto Antônio (Universidade Federal de Goias, 2020)
This work questions the relationship between rural education and agroecology in rural settlement areas linked to the Brazilian Landless Workers’ Movement (MST). It starts off from the assumption that agroecology, as a productive matrix spread by the MST, strengthens and increases the perspective of emancipatory rural education, which values individuals’ knowledge and lifestyle, besides its contribution to their continuity in the countryside. Thus, the school takes a main role in the process of formal education and becomes a privileged space to study the contradictions within the Brazilian rural context, as well as the dissemination of agroecology principles. The school, however, is unable to ensure this education if it does not follow the movement from the reality in which it takes part. Therefore, supported by literature review, documental analyses, interviews and in loco observations, this text presents an analysis of agroecological actions developed in two rural schools located in rural settlement areas in the State of Paraná by contextualizing the progresses and limitations of its pedagogical practices.
Las interfaces entre la educación del campo y la agroecología en áreas de asentamientos rurales en el estado de paraná
Interfaces entre a educação do campo e a agroecologia em áreas de assentamentos rurais no estado do paraná
Keywords: Agroecology; Rural Education; Rural Settlement